FACTORS AFFECTING THE QUALITY OF POSTGRADUATE RESEARCH IN STATE AGRICULTURAL UNIVERSITIES (SAUs) - T. SRINIVAS*, T. V. SRIDHAR, P. PUNNA RAO; T. RAMESH BABU (The Journal of Research ANGRAU, 2019)
The study conducted on assessing the quality of postgraduate research revealed that the student research is being amply published and on an average two publications are being brought out from each thesis. From postgraduate research, more than 60 per cent of the publications were published in journals having NAAS rating <4.0 in both the universities viz., Acharya N G Ranga Agricultural University (ANGRAU) and Tamilnadu Agricultural University (TNAU). The articles published during the last five years of research from 2011-2016 having NAAS rating above 6.0 are only 5.32% and 8.05% in ANGRAU and TNAU, respectively. Majority of the faculty opined that innovativeness and specialization are playing a major role in identifying research topic.Lack of participation in appropriate forums,lack of sufficient funding and infrastructure facilities are the main reasons affecting the quality of PG research.